MERCOSUR, agenda de temas y debate de ideas en la segunda década del siglo XXI - Lincoln Bizzozero (Meridiano 47, 2013)
This contribution examines MERCOSUR regionalism, the agenda items and discussion of ideas. Two questions arise: the autonomy of national political systems and civil society against the state in generating regional agenda topics and discussions of regionalization.